Meningitis due to non-steroidal anti-inflammatory drugs: an often-overlooked complication of a widely used medication. Issue 11 (7th November 2019) - Desgranges, Florian; Tebib, Nathalie; Lamy, Olivier; Kritikos, Antonios
Abstract : A 40-year-old man developed aseptic meningitis after ibuprofen consumption for tension-type headaches. After a thorough diagnostic workup and lack of improvement on empirical therapy for common aetiologies of meningitis (bacterial and viral infections), we suspected non-steroidal anti-inflammatory drug (NSAID) induced meningitis due to the temporal relationship between drug administration and symptom onset. Two days after NSAID suppression, the evolution was progressively favourable with complete resolution of fever and symptoms. On follow-up, symptoms did not recur and there was no neurological sequela. This article summarises the clinical picture and the complementary exams that led to the difficult-to-make diagnosis of NSAID-induced acute meningitis, in parallel with a brief review of the literature.